2021
DOI: 10.11646/phytotaxa.498.2.6
|View full text |Cite
|
Sign up to set email alerts
|

<strong>Molecular phylogenetics of <em>Pterocyclus</em> (Apiaceae) based on nrDNA ITS sequences: revised circumscription with a restored species</strong>

Abstract: The genus Pterocyclus Klotzsch, along with many others, constituted the taxonomically complex Pleurospermum s.l. To delimit its circumscription and clarify its interspecific relationships, molecular phylogenetic analysis and detailed specimen examination were carried out. Its status as an independent genus was confirmed, with four species recognized. Pterocyclus wolffianus, the synonymous species of Pterocyclus forrsetii should be restored as an independent species. A new taxonomic account for Pterocyclus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 0 publications
5
10
1
Order By: Relevance
“…The presence of the six lineages within Pleurospermum s. l. and their composition inferred by plastid phylogeny in this study are compatible with previous studies that were inferred from ITS and a few plastid fragments (Zhou et al, 2008;Zhou et al, 2009;Downie et al, 2010;Valiejo-Roman et al, 2012;Guo M. et al, 2020;Guo X-L. et al, 2020;Zhou et al, 2020a;Xu et al, 2021;Zhou et al, 2021).…”
Section: Phylogeny Inferencesupporting
confidence: 92%
See 3 more Smart Citations
“…The presence of the six lineages within Pleurospermum s. l. and their composition inferred by plastid phylogeny in this study are compatible with previous studies that were inferred from ITS and a few plastid fragments (Zhou et al, 2008;Zhou et al, 2009;Downie et al, 2010;Valiejo-Roman et al, 2012;Guo M. et al, 2020;Guo X-L. et al, 2020;Zhou et al, 2020a;Xu et al, 2021;Zhou et al, 2021).…”
Section: Phylogeny Inferencesupporting
confidence: 92%
“…The other two species (P. wilsonii and P. hedinii) in Pleurospermeae and the species in the other five lineages are supposed to be excluded from Pleurospermum. We support the latest revision of Pterocyclus (group B) (Zhou et al, 2021) and Pleurospermopsis (group F) (Zhou et al, 2020a), while the remaining three lineages remain unresolved and need further investigation. On the basis of phylogenetic inference, comparative analyses found that these plastomes are conserved in terms of genome size, genome structure, IR borders, codon bias, and RNA editing sites among taxa.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…was treated as comprising about 50 species widely distributed in northern Asia and East Europe, of which 39 were in China (Pan and Watson 2005). Taxonomic changes by Pimenov and Kljuykov (2000a, b), Pimenov (2017), Pimenov et al (2000) and Zhou et al (2020aZhou et al ( , 2021, have reduced that number considerably. However, relationships among some synonymous species are still ambiguous.…”
Section: Introductionmentioning
confidence: 99%